Mediated By WoM: Service Quality, Price, and Customer Satisfaction - Regina, Dewa Ayu Inmas; Sanica, I Gede (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to determine the effect of service quality and price on customer satisfaction mediated by Word of Mouth. The sample in this study amounted to 105 respondents of Dewa Putu Toris Studio of Artist Painting Gianyar customers. Data were analyzed using the Partial Least Squares (PLS) methodology. Based on the results of this study, it shows that service quality has a significant positive effect on word-of-mouth, prrice has a significant positive effect on word-of-mouth, service quality has a significant positive effect on customer satisfaction. Price has a significant positive effect on customer satisfaction, word of mouth has a positive and significant effect on customer satisfaction, word of mouth mediates the significant positive effect of service quality on customer satisfaction and word of mouth mediates the significant positive effect of price on customer satisfaction at Dewa Putu Toris Studio of Artist Painting Gianyar. These implications suggest that Dewa Putu Toris Studio should adopt an integrated approach to managing service quality, pricing, and word-of-mouth to maximize customer satisfaction and potentially drive business growth.